A soluble germanium chelate catalyst and its preparation method and use
By chelating germanium dioxide with an aqueous solution of a specific acid, a soluble germanium chelate catalyst is generated, which solves the problem that existing catalysts are difficult to improve the viscosity and hue quality of PETG and PCTG products at the same time, and achieves efficient polymerization catalysis. It also avoids catalyst deposition, ensuring long-term and stable operation of the device.
Patent Information
- Application Number
- CN202410166670.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-02-06
AI Technical Summary
During the polymerization of PETG and PCTG, it is difficult for existing catalysts to simultaneously improve the viscosity and hue quality of the product, and the solid phase of the germanium dioxide catalyst leads to deposition, affecting the long-term operation of the device.
By chelating germanium dioxide with an aqueous solution of a specific type of acid, a soluble germanium chelate catalyst is generated. This catalyst is used to catalyze the polymerization of PETG or PCTG, which can significantly improve the viscosity and hue quality of the product and maintain the catalyst's Soluble, avoiding deposition.
It is achieved to significantly improve the viscosity and hue quality of the product during PETG or PCTG polymerization, while avoiding catalyst deposition, ensuring the stability of the device's long-term operation and reducing the cost of the catalyst.
Smart Images

Figure BDA0004699870360000031 
Figure BDA0004699870360000032 
Figure BDA0004699870360000033
Abstract
Description
Technical Field
[0001] The invention relates to a soluble germanium chelate catalyst and a preparation method and application thereof. Background Art
[0002] PETG and PCTG are both transparent, non-crystalline copolyesters. Both can be prepared by esterification and polymerization of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM in the presence of an esterification catalyst and a polymerization catalyst. The two can be distinguished according to the different molar proportions of the segments corresponding to CHDM in the total diol (CHDM and EG) segments in the copolyester. Generally, the polymerization product with a molar proportion of 31% to 32% of the segments corresponding to CHDM is called PETG copolyester; and the polymerization product with a molar proportion of 60% to 62% of the segments corresponding to CHDM is called PCTG. Both polymerization products have high transparency, good toughness and impact strength, excellent low-temperature toughness, high tear resistance, good processing performance, and excellent chemical resistance. Both can be processed by traditional extrusion, injection molding, blow molding, and blister molding. Both can be widely used in the market of plates and sheets, high-performance shrink films, bottles, and profiles; they can also be used to produce toys, household utensils, and medical supplies.
[0003] The catalysts used to catalyze the esterification and polymerization of PETG and PCTG generally include antimony catalysts, titanium catalysts, germanium catalysts, tin catalysts, etc. When catalyzing the synthesis of PETG and PCTG, the brightness and non-crystalline properties of the polymer product are crucial.
[0004] Antimony-based catalysts are the cheapest and have good catalytic polymerization activity. However, they are prone to reduction reactions to generate antimony ash during high-temperature reactions, which can cause the hue L value of PETG and PCTG polymer products to be very low (generally ≤56.0) and the b value to be high (generally ≥4.0), resulting in poor product appearance hue. The L value of the product cannot be improved by colorants, so antimony-based catalysts are usually not used alone during polymerization.
[0005] Titanium-based catalysts are highly active, but they also catalyze high levels of side reactions, resulting in more by-products in the product, a yellowish hue, and a high b value. Even with the use of colorants for adjustment, the product hue is very poor, so titanium-based catalysts are usually not used alone during polymerization.
[0006] Tin-based catalysts also have problems with poor sunlight fastness and yellowing of slices. In addition, tin catalysts are toxic and cause serious environmental pollution.
[0007] Germanium catalysts are the most commonly used catalysts for the synthesis of PETG and PCTG. They are usually used alone or in combination with other catalysts. They have a mild catalytic effect, low level of side reactions, and good hue for polymer products, usually with an L value of ≥63.5 and a b value of ≤1.0.
[0008] Germanium dioxide is the most commonly used germanium-based catalyst. Although it has the aforementioned advantages, it has a very high hardness and it is usually difficult to crush the germanium dioxide powder to a particle size below 0.1-0.3um required for solid-phase catalysts. The particle size of commercially available germanium dioxide powder is usually ≤75μm. This particle size is too large. If the germanium dioxide powder is added in the late stage of esterification of the self-polymerization system, the polymerization reaction cannot be completed due to poor catalytic effect.
[0009] The existing method of using germanium dioxide is to add germanium dioxide powder to distilled water under stirring conditions and reflux for a long time to make the germanium dioxide react with water to form germanic acid (H 2 GeO 3 or Ge(OH) 4 ), the general configuration concentration is only about 1.0%. And germanium dioxide crystals include three types: hexagonal, tetragonal and amorphous, among which only the tetragonal is slightly soluble in water, and the other two are difficult to dissolve. In addition, the specific gravity of the hexagonal crystal is 4.228, and the specific gravity of the tetragonal crystal is 6.239. Even if it is added to the polymerization system in the form of the aforementioned germanic acid, it is easy to dehydrate and return to the solid phase of germanium dioxide under the high temperature conditions of the esterification and polymerization stages. After a long time, it will be deposited in places such as the reactor wall and the melt pipe, affecting the long-term operation of the device.
[0010] Chinese patent CN104640905A discloses using titanium compounds and germanium compounds as composite catalysts for catalyzing PCTG. Although the hue of the product can be improved, the hue performance of the product still needs to be improved.
[0011] Chinese patent CN113429549B discloses a composite catalyst for catalyzing the polymerization of polycyclohexylene dimethylene terephthalate, wherein the catalyst is a metal / non-metal composite, which is a first catalyst Zr-Te-P, a second catalyst Si-Zr-B or a third catalyst Si-Zr-Sn-Ba. Although the composite catalyst can increase the polymerization reaction rate and reduce the occurrence of side reactions, the hue performance of the product still needs to be improved.
[0012] Chinese patent CN116693830B discloses a quaternary ammonium titanium / zirconium chelate catalyst prepared by reacting 2,3-dihydroxypropyl-trimethylammonium chloride with tetrabutyl titanate or tetrabutyl zirconate, which is used to catalyze the copolymerization of modified PETG. Although the color of the copolyester product is good, the structure of the catalyst is relatively complex and the preparation process is relatively complicated.
[0013] Chinese patent CN1121727A discloses a composite catalyst of manganese diacetate, zinc acetate, isopropoxy titanium and germanium dioxide, but the viscosity of PETG prepared by the composite catalyst is not high enough. Summary of the invention
[0014] The invention aims to provide a method for preparing a soluble germanium chelate catalyst. When the catalyst obtained by the preparation method is used to catalyze the polymerization of PETG or PCTG, the viscosity and various hue qualities of the product can be significantly improved. The catalyst is soluble and will not be deposited on the wall of the reactor or the melt pipeline, and will not affect the long-term operation of the device.
[0015] In order to achieve the above object, the technical solution adopted by the present invention is:
[0016] A method for preparing a soluble germanium chelate catalyst comprises the following steps: reacting germanium dioxide with an aqueous solution of an acid to generate a clear solution containing a germanium chelate, wherein the clear solution comprises an excess of acid; adding a Lewis base to the clear solution to neutralize the excess acid to obtain an aqueous solution of the germanium chelate; post-treating the aqueous solution of the germanium chelate to obtain the soluble germanium chelate catalyst; the acid is selected from a combination of one or more of a dibasic acid, and a C3-C6 dibasic acid or a tribasic acid containing a hydroxyl group or an amine group.
[0017] In the present invention, when preparing the aqueous solution of the aforementioned acid, the dissolution rate can be accelerated by heating or the like.
[0018] In some embodiments, the acid is selected from a combination of one or more of citric acid, tartaric acid, glutamic acid, gluconic acid, L-lactic acid and oxalic acid.
[0019] In some embodiments, when the acid is selected from a combination of multiple acids, it is best to contain oxalic acid. Preferably, in the mixed acid, the molar ratio of other acids to oxalic acid is 1:1-3.
[0020] In the prior art, germanium dioxide powder is difficult to dissolve in water and cannot be prepared into a clear aqueous solution. When used for catalytic polymerization, germanium dioxide is usually reacted with water to form germanic acid by reflux, but the concentration of the germanic acid is low, and when added to the polymerization system in the form of germanic acid, it is also easy to dehydrate and return to the solid phase of germanium dioxide under the high temperature conditions of the esterification and polymerization stages, which leads to the deposition of germanium dioxide on the wall of the reactor and the melt pipe, which is not conducive to the long-term operation of the device on the one hand, and also affects the polymerization catalytic effect on the other hand, and is not conducive to the color of the polyester product.
[0021] The present invention carries out chelate reaction with the aqueous solution of germanium dioxide and the acid of specific type, the acid of the present invention is selected from diprotic acid, especially oxalic acid and one or more combinations in diprotic acid or triprotic acid of C3-C6 containing hydroxyl or amido, wherein oxalic acid does not contain hydrophobic alkyl segment, other diprotic acid or triprotic acid has hydrophilic hydroxyl or amido, and carbon chain is shorter, and hydrophilicity is strong. Two carboxyl groups in these acids can carry out chelate reaction with the germanium atom in germanium dioxide, generate corresponding germanium chelate, and hydroxyl or amido in acid raw material can increase the hydrophilicity of germanium chelate, make the germanium chelate generated by reaction soluble in water, can obtain clarified germanium chelate aqueous solution, and then can prepare soluble germanium chelate catalyst of the present invention. If acid has long hydrophobic alkyl segment, then its hydrophilicity is not enough, and may cause germanium chelate to be unable to be completely dissolved in water.
[0022] When the acid is citric acid, the reaction equation is as follows:
[0023]
[0024] When the acid is tartaric acid, the reaction equation is as follows:
[0025]
[0026] When the acid is oxalic acid, the reaction equation is as follows:
[0027]
[0028] In some embodiments, the structure of the germanium dioxide is selected from hexagonal, anatase or amorphous.
[0029] In some embodiments, the particle size of the germanium dioxide is 0.1 to 75 μm, preferably 0.1 to 50 μm, and more preferably 0.1 to 5 μm.
[0030] In some embodiments, the molar ratio of the germanium dioxide to the acid is 1:1.0-5.0; preferably 1:1.8-3.5, and more preferably 1:2.2-2.6.
[0031] In some embodiments, the reaction is carried out at 30-100°C.
[0032] In some embodiments, the reaction time is 2 to 6 hours.
[0033] In some embodiments, the reaction is carried out in a reactor equipped with a reflux cooling system, and the water vapor generated by the reaction is refluxed into the reactor; as the reaction proceeds, germanium dioxide gradually reacts to form germanium chelate and dissolves in water, and the reaction system gradually changes from a white suspension to a clear and transparent state. That is, a stable germanium chelate aqueous solution is formed, and the aqueous solution will not produce precipitation when placed at room temperature. The aqueous solution is a stable homogeneous system.
[0034] In some embodiments, the mass concentration of the germanium chelate in the aqueous solution is 0.5-12.0%. Depending on the acid chelating agent, the solubility of the obtained germanium chelate in the aqueous solution may be different, preferably 1.0-10.0%, most preferably 2.0-8.0%.
[0035] In some embodiments, the post-treatment includes adding ethylene glycol to the aqueous solution of the germanium chelate to obtain a water / ethylene glycol mixed solution of the germanium chelate. The liquid catalyst solution obtained by adding ethylene glycol EG to the aqueous solution can be used directly to catalyze PETG / PCTG esterification and polymerization reactions. This is the first form of the catalyst of the present application, namely the liquid form.
[0036] In some embodiments, after adding Lewis base for neutralization, the pH value of the clear solution is 5.5 to 7.0, preferably 5.8 to 6.8, and more preferably 6.2 to 6.5.
[0037] In some embodiments, the Lewis base is selected from a combination of one or more of sodium hydroxide, lithium hydroxide, potassium hydroxide, sodium acetate, calcium acetate, zinc acetate, lithium acetate, manganese acetate, cobalt acetate, sodium carbonate, sodium bicarbonate, magnesium hydroxide and aluminum hydroxide.
[0038] In some embodiments, the post-treatment includes the steps of cooling the aqueous solution of the germanium chelate, standing for crystallization, filtering, washing, and drying. The catalyst obtained by the second post-treatment method is in a crystalline state. When the catalyst in the crystalline state is subsequently used for catalytic polymerization, it still needs to be dissolved in a mixed solvent of water and ethylene glycol, but the catalyst in the crystalline state is convenient for storage and transportation. The purified soluble chelated germanium salt can further remove excess acid in the reaction process and eliminate the effects of increased esterification and polymerization side reactions caused by residual acid. In turn, the quality of the copolyester product can be greatly improved, and the product hue can be significantly improved.
[0039] In some embodiments, the temperature after cooling is -20 to 0°C.
[0040] In some embodiments, the washing is performed in anhydrous alcohol at 50-70° C., and the excess acid is further removed by washing.
[0041] In some embodiments, the washing time is 2 to 4 hours.
[0042] In some embodiments, during washing, the mass ratio of the crystals to anhydrous alcohol is 1:1-2.
[0043] In some embodiments, the post-treatment further comprises dissolving the germanium chelate crystals in a certain amount of water under stirring conditions at 60-80° C., adding ethylene glycol after the dissolution is complete, and continuing to stir evenly to obtain the catalyst.
[0044] In some embodiments, in the soluble germanium chelate catalyst, the mass ratio of water to ethylene glycol is 1:4 to 4:1, preferably 3.5:6.5 to 6.5:3.5, and more preferably 4.5:5.5 to 5.5:4.5.
[0045] In some embodiments, the addition of ethylene glycol is preferably carried out under stirring. The addition of ethylene glycol can reduce the water content in the catalyst solution, ensuring that the catalyst can be directly injected into the polymerization reaction system in the later stage of the esterification reaction.
[0046] In some embodiments, in the catalyst solution prepared by redissolving the crystals in water and ethylene glycol, the mass concentration of the germanium chelate is 0.5% to 14.0%, preferably 1.0% to 10.0%, and more preferably 2.0% to 8.0%. EG is added to the catalyst solution again before use to control the final content of the soluble chelated germanium salt in the mixed solvent water / EG to be 1.0 to 3.0%, which is convenient for catalyst injection into industrial equipment under this concentration condition.
[0047] The present invention also provides a soluble germanium chelate catalyst prepared by the preparation method of the soluble germanium chelate catalyst. When the catalyst is used to catalyze the polymerization of PETG or PCTG, the viscosity and various hue qualities of the product can be significantly improved, and the catalyst is soluble and will not be deposited on the wall of the reactor or the melt pipe, and will not affect the long-term operation of the device.
[0048] The present invention also provides the use of the soluble germanium chelate catalyst for catalyzing polyester synthesis.
[0049] In some embodiments, during the synthesis of polyester, the soluble germanium chelate catalyst is used alone, or the soluble germanium chelate catalyst is used together with a titanium-based catalyst.
[0050] In some embodiments, the polyester is selected from PETG or PCTG.
[0051] In the present invention, PETG refers to a copolyester of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM, and in the copolyester, the segment corresponding to CHDM accounts for 31% to 32% by mole in the total diol (CHDM and EG) segment; PCTG refers to a copolyester of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM, and in the copolyester, the segment corresponding to CHDM accounts for 60% to 62% by mole in the total diol (CHDM and EG) segment.
[0052] When the catalyst of the present invention is used for the above purposes, it has better catalytic activity and reaction efficiency. The catalyst maintains a stable homogeneous state during esterification and polymerization, and can catalyze polymerization reactions more efficiently. Compared with solid-phase germanium dioxide, the efficiency is improved by 15-20%.
[0053] In some embodiments, the soluble germanium chelate catalyst is used alone as an esterification catalyst and a polymerization catalyst. The esterification catalyst accounts for 5 to 15 ppm of the polymer mass, and the polymerization catalyst accounts for 50 to 70 ppm of the polymer mass, calculated as germanium dioxide.
[0054] In some embodiments, the soluble germanium chelate catalyst is used together with a titanium-based catalyst, and the titanium element in the titanium-based catalyst and the germanium element in the soluble germanium chelate catalyst account for 1 to 35 ppm and 150 to 10 ppm of the polymer mass, respectively, preferably 3 to 20 ppm and 100 to 25 ppm; the more optimized dosage range is: 5 to 15 ppm and 50 to 35 ppm.
[0055] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0056] The present invention conducts a chelation reaction between germanium dioxide and an aqueous solution of a specific type of acid, and selects a dibasic acid or tribasic acid with strong hydrophilicity and chelation effect, and the two carboxyl groups in these acids can conduct a chelation reaction with the germanium atoms in the germanium dioxide to generate corresponding germanium chelates, and the hydroxyl or amine group in the acid raw material can increase the hydrophilicity of the germanium chelate, so that the germanium chelate generated by the reaction can be soluble in water, and a clear germanium chelate aqueous solution can be obtained, so that the soluble germanium chelate catalyst of the present invention is a dissolved germanium chelate solution state. When it is used to catalyze polyester synthesis, solids will not be deposited on the wall of the reactor or the melt pipeline, and the long-term operation of the device will not be affected.
[0057] The soluble germanium chelate catalyst of the present invention has high stability and will not produce precipitation even if placed at room temperature for 2 months. When the acid is citric acid, the corresponding catalyst will not produce precipitation even if placed at 100-280°C for 1 month, and has excellent stability and heat resistance.
[0058] The soluble germanium chelate catalyst of the present invention can maintain a homogeneous solution state during the whole process of esterification and polymerization, and its catalytic efficiency is better than that of traditional germanium catalysts such as germanium dioxide, and its catalytic activity can be increased by 15% to 20%. While ensuring the same catalytic efficiency, the amount of germanium catalyst used can be effectively reduced. Germanium catalysts are expensive, so this can significantly reduce the cost of the catalyst.
[0059] When the acid is in chemical excess, the excess acid is removed during the preparation of the catalyst in the present invention, thereby avoiding the adverse effect of the excess acid on the hue of the polyester product.
[0060] When the soluble germanium chelate catalyst of the invention is used to catalyze the copolymerization synthesis of PETG or PCTG, a polyester product with high viscosity and good color quality can be obtained. DETAILED DESCRIPTION
[0061] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions used in the examples can be further adjusted according to specific requirements, and the unspecified implementation conditions are usually the conditions in conventional experiments. Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art.
[0062] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0063] Example 1
[0064] This embodiment provides a soluble germanium chelate catalyst, and uses it in the polymerization of PETG or PCTG, and the specific steps are as follows:
[0065] Preparation of catalyst:
[0066] A certain amount of distilled water is injected into a reactor equipped with a reflux cooling system, stirring is started and the temperature is raised to 70°C, and the weighed tartaric acid is added to the reactor, and stirred and dissolved for 2.0 hours. Then the weighed germanium dioxide powder is slowly added to the reactor, and the water vapor generated during the reaction process is returned to the reactor after reflux cooling. During the reaction process, germanium dioxide gradually reacts to form germanium chelate and dissolves in water. After 2.0 hours of reaction, the white suspension gradually becomes clear and transparent to form a stable tartaric acid chelated germanium salt aqueous solution. The aqueous solution is placed at room temperature for 2 months without precipitation. The mass concentration of tartaric acid chelated germanium salt in the aqueous solution is controlled to be 13.08%. Sodium acetate is used to adjust the pH value of the chelated germanium salt aqueous solution to 6.5. Under stirring conditions, the temperature of the chelated germanium salt aqueous solution is maintained at 80°C, and ethylene glycol EG is metered into it to obtain a tartaric acid chelated germanium salt catalyst solution, in which the mass concentration of tartaric acid chelated germanium salt is 7.05% (the content is ~2.0% in terms of germanium dioxide).
[0067] PETG polymerization:
[0068] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0069] First, pure terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation, and the prepared tartaric acid chelated germanium salt catalyst solution was injected into the slurry delivery pipeline. Liquid, as an esterification catalyst, its total mass dosage of the melt: 10ppm (in terms of germanium dioxide), the prepared slurry is transported to the esterification kettle one through a screw metering pump, the temperature in the esterification kettle one is controlled at 254-255°C, the process tower pressure is: 70-80kpa (positive pressure), the esterification kettle two is a multi-chamber design with three sub-chambers, which is convenient for adding various additives, the above-prepared tartaric acid chelated germanium salt catalyst solution is added to the second chamber of the esterification kettle two as a polymerization catalyst (addition in the second chamber is conducive to evaporating the water in the catalyst), the polymerization catalyst accounts for 60pp of the total mass of the melt m (in terms of germanium dioxide), toner and stabilizer (phosphate, etc.) are added to the three esterification chambers, the two esterification kettles are atmospheric pressure reactors, and the esterification temperatures of the three chambers are controlled as follows: 255-256°C for the first chamber, 253-254°C for the second chamber, and 257-258°C for the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with an inner and outer chamber design, and the reaction temperature of the first prepolymerization kettle is controlled at 258-260°C, and the vacuum degree is 9.0Kpa. The oligomers polymerized in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor The reactor is used to control the reaction temperature of the second prepolymerization kettle: 260-262°C. The prepolymer after the reaction of the second prepolymerization kettle is introduced into the high-viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high-viscosity final polymerization reactor is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 265-268°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 635-650 Pa.s, and the outlet PETG intrinsic viscosity is controlled at 0.779 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PETG slice indicators are as shown in Table 1.
[0070] Or PCTG polymerization:
[0071] Continuous polymerization is carried out on a 30,000 ton / year PCTG continuous polymerization unit, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0072] First, pure terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) are accurately measured for slurry preparation, and the tartaric acid chelated germanium salt catalyst solution prepared above is injected into the slurry conveying pipeline as an esterification catalyst, and its total mass dosage of the melt is: 10ppm (in terms of mass) The prepared slurry is transported to the first esterification kettle through a screw metering pump, and the temperature in the first esterification kettle is controlled at 256-257°C. The process tower pressure is 70-80kpa (positive pressure). The second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. The above-prepared tartaric acid chelated germanium salt catalyst solution is added to the second chamber of the second esterification kettle as a polymerization catalyst (adding from the second chamber is conducive to evaporating the water in the catalyst to prevent the moisture in the catalyst from being detrimental to the polymerization; the solubility of germanium chelate in pure ethylene glycol is not high. In order to make the germanium chelate soluble, water and ethylene glycol are used in the preparation of the catalyst. As a mixed solvent), the amount of polymerization catalyst in the total mass of the melt is 60ppm (in terms of germanium dioxide), toner and stabilizer (phosphate, etc.) are added to the esterification three-chamber, the esterification two-kettle is a normal pressure reactor, and the esterification temperatures of the three compartments are respectively controlled as follows: 255-256°C for the first chamber, 253-254°C for the second chamber, and 260-262°C for the third chamber; the esterified materials after the esterification reaction are introduced into the prepolymerization kettle, which is a vertical stirring structure with an inner and outer chamber design, and the reaction temperature of the prepolymerization kettle is controlled to be 266-268°C, and the vacuum degree is 9.0Kpa. The oligomers polymerized in the prepolymerization kettle are introduced into the prepolymerization kettle. The second prepolymerization reactor is a single-axis horizontal disc reactor, and the reaction temperature of the second prepolymerization reactor is controlled at 272-274°C. The prepolymer after the reaction of the second prepolymerization reactor is introduced into the high-viscosity final polymerization reactor through a prepolymer melt pump and a prepolymer filter. The high-viscosity final polymerization reactor is a front and rear double-axis horizontal disc reactor, and its reactor outlet temperature is controlled at 280-282°C, vacuum degree is 90-110 Pa, outlet melt dynamic viscosity is controlled at 600-620 Pa.s, and outlet PCTG characteristic viscosity is controlled at 0.802 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.
[0073] Example 2
[0074] Embodiment 2 provides a soluble germanium chelate catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Embodiment 1, except that: when preparing the catalyst, tartaric acid is replaced with citric acid, and the mass concentration of citric acid chelated germanium salt in the aqueous solution is controlled to be 16.06%. After adding EG, the mass concentration of citric acid chelated germanium salt in the final catalyst solution is 8.66% (the content is ~2.0% in terms of germanium dioxide). Among them, the citric acid chelated germanium salt aqueous solution is placed at 280°C for 3 months without precipitation. It has excellent stability and heat resistance. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in Tables 1-2 below.
[0075] Example 3
[0076] Embodiment 3 provides a soluble germanium chelate catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Embodiment 1, except that: when preparing the catalyst, tartaric acid is replaced with glutamic acid, and the mass concentration of glutamic acid chelated germanium salt in the aqueous solution is controlled to be 12.87%. After adding EG, the mass concentration of glutamic acid chelated germanium salt in the final catalyst solution is 6.94% (the content is ~2.0% in terms of germanium dioxide). Among them, the glutamic acid chelated germanium salt aqueous solution is placed at room temperature for 1 month without precipitation. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in Tables 1-2 below.
[0077] Example 4
[0078] Embodiment 4 provides a soluble germanium chelate catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Embodiment 1, except that: when preparing the catalyst, tartaric acid is replaced with oxalic acid, and the mass concentration of the oxalic acid chelated germanium salt in the aqueous solution is controlled to be 8.82%. After adding EG, the mass concentration of the oxalic acid chelated germanium salt in the final catalyst solution is 4.76% (the content is ~2.0% in terms of germanium dioxide). Among them, the oxalic acid chelated germanium salt aqueous solution is placed at room temperature for 3 months without precipitation. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in Tables 1-2 below.
[0079] Example 5
[0080] Embodiment 5 provides a soluble germanium chelate catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Embodiment 1, except that: when preparing the catalyst, tartaric acid is replaced with a mixed acid of tartaric acid and oxalic acid, wherein the molar ratio of tartaric acid to oxalic acid is 1:2. And the mass concentration of the mixed acid chelated germanium salt in the aqueous solution is controlled to be 10.24%. After adding EG, the mass concentration of the mixed acid chelated germanium salt in the final catalyst solution is 5.52% (the content is ~2.0% in terms of germanium dioxide). Among them, the mixed acid chelated germanium salt aqueous solution is placed at room temperature for 3 months without precipitation. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in Tables 1-2 below.
[0081] Example 6
[0082] Embodiment 6 provides a soluble germanium chelate catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Embodiment 1, except that: when preparing the catalyst, tartaric acid is replaced with a mixed acid of citric acid and oxalic acid, wherein the molar ratio of citric acid to oxalic acid is 1:3. And the mass concentration of the mixed acid chelated germanium salt in the aqueous solution is controlled to be 10.63%. After adding EG, the mass concentration of the mixed acid chelated germanium salt in the final catalyst solution is 5.73% (the content is ~2.0% in terms of germanium dioxide). Among them, the mixed acid chelated germanium salt aqueous solution is placed at room temperature for 3 months without precipitation. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in Tables 1-2 below.
[0083] Example 7
[0084] Example 7 The soluble germanium chelate catalyst of Example 1 and a conventional titanium catalyst are used in combination for the polymerization of PETG or PCTG, and the specific steps are as follows:
[0085] PETG polymerization:
[0086] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0087] First, the purified terephthalic acid PTA, ethylene glycol EG and molten 1,4-cyclohexanedimethanol CHDM are accurately measured and prepared in a molar ratio of PTA:EG:CHDM=1:0.93:0.32, and a total molar ratio of PTA:(EG+CHDM)=1:1.25. Titanium-based catalyst tetrabutyl titanate is injected into the slurry conveying pipeline as an esterification catalyst, and its total mass dosage of the melt is 3ppm (in terms of titanium element). The prepared slurry is conveyed to the esterification kettle 1 via a screw metering pump, and the temperature in the esterification kettle 1 is controlled at 254-255°C, and the process tower pressure is 7 0~80kpa (positive pressure), the esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. The tartaric acid chelated germanium salt catalyst solution of Example 1 is added to the second chamber of the esterification kettle as a part of the polymerization catalyst (the addition in the second chamber is conducive to evaporating the water in the catalyst), which accounts for 40ppm (in terms of germanium dioxide) of the total mass of the melt, and the third chamber of the esterification kettle is added with a toner and a stabilizer (phosphate ester, etc.). At the same time, the titanium catalyst tetrabutyl titanate is added to the third chamber of the esterification kettle as a part of the polymerization catalyst, which accounts for 12ppm (in terms of titanium element) of the total mass of the melt. The second esterification kettle is a normal pressure reactor, and the esterification temperatures of the three chambers are controlled as follows: 255-256°C for chamber one, 253-254°C for chamber two, and 257-258°C for chamber three; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs, and the reaction temperature of the first prepolymerization kettle is controlled at 258-260°C, and the vacuum degree is 9.0Kpa; the oligomers polymerized in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor, and the reaction temperature of the second prepolymerization kettle is controlled at 26 0~262℃, the prepolymer after the reaction in the second prepolymerization kettle is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 265~268℃, the vacuum degree is 90~110Pa, the outlet melt dynamic viscosity is controlled at 635~650Pa.s, and the outlet PETG intrinsic viscosity is controlled at 0.783 (measured in a mixed solvent with a volume ratio of phenol:tetrachloroethane of 3:2). The PETG slice indicators are shown in Table 1.
[0088] Or PCTG polymerization:
[0089] Continuous polymerization is carried out on a 30,000 ton / year PCTG continuous polymerization unit, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0090] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.63:0.63 and a total molar ratio of PTA:(EG+CHDM) = 1:1.26. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, and its total mass dosage of the melt was 3ppm (in terms of titanium element). The prepared slurry was delivered to the first esterification kettle via a screw metering pump. The temperature in the first esterification kettle was controlled at 256-257°C and the pressure of the process tower was: 70~80kpa (positive pressure), the second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. The tartaric acid chelated germanium salt catalyst solution of Example 1 is added to the second chamber of the second esterification kettle as a part of the polymerization catalyst (the addition in the second chamber is conducive to evaporating the water in the catalyst), which accounts for 40ppm (in terms of germanium dioxide) of the total mass of the melt, and the toner and stabilizer (phosphate ester, etc.) are added to the third chamber of the esterification kettle. At the same time, the titanium catalyst tetrabutyl titanate is added to the third chamber of the second esterification kettle as a part of the polymerization catalyst, which accounts for 12ppm (in terms of titanium element) of the total mass of the melt. The second esterification kettle is a normal pressure reactor, and the esterification temperatures of the three chambers are controlled as follows: 255-256°C in the first chamber, 253-254°C in the second chamber, and 260-262°C in the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with an inner and outer chamber design, and the reaction temperature of the first prepolymerization kettle is controlled at 266-268°C, and the vacuum degree is 9.0Kpa. The oligomers polymerized in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor, and the reaction temperature of the second prepolymerization kettle is controlled at 27 2~274℃, the prepolymer after the reaction in the second prepolymerization kettle is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 280~282℃, the vacuum degree is 90~110Pa, the outlet melt dynamic viscosity is controlled at 600~620Pa.s, and the outlet PCTG intrinsic viscosity is controlled at 0.802 (measured in a mixed solvent with a volume ratio of phenol:tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.
[0091] Example 8
[0092] Example 8 provides a soluble germanium chelate catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 1, except that when preparing the catalyst, sodium acetate is not used to adjust the pH, but concentration, crystallization, and hot ethanol washing are used to remove excess acid. The steps for preparing the catalyst are as follows:
[0093] Inject a certain amount of distilled water into a reactor equipped with a reflux cooling system, start stirring and heat to 70°C, add the weighed tartaric acid into the reactor, and stir and dissolve for 2.0 hours. Then slowly add the weighed germanium dioxide powder into the reactor, and the water vapor generated during the reaction process returns to the reactor after reflux cooling. During the reaction, germanium dioxide gradually reacts to form germanium chelate and dissolves in water. After 2.0 hours of reaction, the white suspension gradually becomes clear and transparent, forming a stable tartaric acid chelated germanium salt aqueous solution. The aqueous solution is placed at room temperature for 2 months without precipitation. The mass concentration of tartaric acid chelated germanium salt in the aqueous solution is controlled to be 13.08%.
[0094] The tartaric acid chelated germanium salt aqueous solution is concentrated and slowly cooled to -20°C, allowed to stand for crystallization, filtered and collected, vacuum dried, and then crushed. The crushed crystals are dissolved in 70°C anhydrous ethanol under stirring conditions, the mass ratio of crystals to anhydrous ethanol is controlled to be 1:2.0, stirred for 4.0 hours, and then filtered, the excess tartaric acid in the raw material is dissolved in anhydrous ethanol, and the obtained filtrate is cooled and recrystallized again. For the undissolved crystalline solid obtained by filtration, the steps of dissolving, cooling and recrystallizing are repeated again. The crystals obtained twice are combined, vacuum dried, and crushed to obtain soluble tartaric acid chelated germanium salt crystals.
[0095] Under stirring conditions, the aforementioned tartaric acid chelated germanium salt crystals were dissolved in hot distilled water at 80°C, with the mass ratio of crystals to distilled water being 1:6.59. After the crystals were completely dissolved in distilled water for 1 hour, EG was added to the aqueous solution under stirring, and stirring was continued for 2 hours to obtain a tartaric acid chelated germanium salt catalyst solution, in which the mass concentration of the tartaric acid chelated germanium salt was 7.05% (the content was ~2.0% in terms of germanium dioxide).
[0096] When used for the polymerization of PETG or PCTG, the results are shown in Table 1-2 below.
[0097] Examples 9-13
[0098] Examples 9-13 provide a soluble germanium chelate catalyst, and use it in the polymerization of PETG or PCTG. The specific steps are basically the same as those of Examples 2-6, except that when preparing the catalyst, sodium acetate is not used to adjust the pH, but concentration, crystallization, and recrystallization are used to remove excess acid. The specific operation of removing excess acid by concentration, crystallization, and recrystallization is the same as that of Example 8.
[0099] Embodiment 14
[0100] Example 14 The soluble germanium chelate catalyst crystals of Example 8 and a conventional titanium catalyst were used in combination for the polymerization of PETG or PCTG, and the specific operation was the same as that of Example 7. The results are shown in Table 1-2 below.
[0101] Comparative Example 1
[0102] Comparative Example 1 provides a polymerization method for PETG or PCTG, and its polymerization steps are basically the same as those in Example 1, except that: both the esterification and polymerization catalysts are replaced with germanium dioxide aqueous solution, and the amount of catalyst used is increased. The germanium dioxide aqueous solution is prepared by the following method: germanium dioxide powder is added to distilled water, and a reflux reaction is carried out for 8 to 10 hours, so that germanium dioxide reacts with water to form germanic acid. The mass concentration of germanium dioxide is 0.8%. The esterification catalyst accounts for 15ppm (in terms of germanium dioxide) of the total mass of the melt, and the polymerization catalyst accounts for 120ppm (in terms of germanium dioxide) of the total mass of the melt. The polymerization results are shown in Table 1-2 below.
[0103] Comparative Example 2
[0104] Comparative Example 2 provides a polymerization method for PETG or PCTG, and its polymerization steps are basically the same as those in Example 1, except that: the esterification and polymerization catalysts are both replaced with a solution of germanium dioxide water / EG mixed solvent, and the amount of catalyst used is increased. The solution of germanium dioxide water / EG mixed solvent is prepared by the following method: germanium dioxide powder is added to distilled water, heated until the germanium dioxide powder is completely dissolved, EG is added thereto under stirring, the mass ratio of water to EG is 1:1, and stirring and dissolving is continued to obtain a solution of a mixed solvent. In the solution, the mass concentration of germanium dioxide is 0.8%. The esterification catalyst accounts for 15ppm (in terms of germanium dioxide) of the total mass of the melt, and the polymerization catalyst accounts for 120ppm (in terms of germanium dioxide) of the total mass of the melt. The polymerization results are shown in Table 1-2 below.
[0105] Comparative Example 3
[0106] Comparative Example 3 provides a polymerization method of PETG or PCTG, and the polymerization steps are basically the same as those in Example 1, except for the types of esterification and polymerization catalysts (titanium-antimony composite catalyst), the timing of addition and the amount thereof, and the polymerization process parameters. The details are as follows:
[0107] PETG polymerization:
[0108] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0109] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.93:0.32 and a total molar ratio of PTA:(EG+CHDM) = 1:1.25. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 3ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was then conveyed through a screw The metering pump is used to transport the liquid to the esterification kettle 1, and the temperature in the esterification kettle 1 is controlled at 254-255°C. The pressure of the process tower is 70-80kpa (positive pressure). The esterification kettle 2 is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. Ethylene glycol antimony is added to the third chamber of the esterification kettle 2 as a polymerization catalyst. The polymerization catalyst accounts for 225ppm (in terms of antimony element) of the total mass of the melt. Toner and stabilizer (phosphate ester, etc.) are added to the third chamber of the esterification kettle. The esterification kettle 2 is a normal pressure reactor, and the esterification temperatures of the three sub-chambers are respectively The control is: 255-256℃ in the first chamber, 253-254℃ in the second chamber, and 257-258℃ in the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs. The reaction temperature of the first prepolymerization kettle is controlled at 262-263℃ and the vacuum degree is 9.0Kpa. The oligomers after polymerization in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor. The reaction temperature of the second prepolymerization kettle is controlled at 264-265℃. The prepolymer after the reaction is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 275-277°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 635-650 Pa.s, and the outlet PETG intrinsic viscosity is controlled at 0.780 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PETG slice indicators are shown in Table 1.
[0110] Or PCTG polymerization:
[0111] Continuous polymerization is carried out on a 30,000 ton / year PCTG continuous polymerization unit, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0112] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.63:0.63, and a total molar ratio of PTA:(EG+CHDM) = 1:1.26. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 3ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was then conveyed through a screw The metering pump is used to transport the liquid to the first esterification kettle, and the temperature in the first esterification kettle is controlled at 256-257°C. The pressure of the process tower is 70-80kpa (positive pressure). The second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. Ethylene glycol antimony is added to the third chamber of the second esterification kettle as a polymerization catalyst. The polymerization catalyst accounts for 240ppm (in terms of antimony element) of the total mass of the melt. Toner and stabilizer (phosphate ester, etc.) are added to the third chamber of the esterification kettle. The second esterification kettle is a normal pressure reactor, and the esterification temperatures of the three sub-chambers are respectively The control is: 255-256℃ in the first chamber, 253-254℃ in the second chamber, and 260-262℃ in the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs. The reaction temperature of the first prepolymerization kettle is controlled at 266-268℃ and the vacuum degree is 9.0Kpa. The oligomers after polymerization in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor. The reaction temperature of the second prepolymerization kettle is controlled at 272-274℃. The prepolymer after the reaction is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 280-282°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 600-620 Pa.s, and the outlet PCTG intrinsic viscosity is controlled at 0.806 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.
[0113] Comparative Example 4
[0114] Comparative Example 4 provides a polymerization method of PETG or PCTG, and the polymerization steps are basically the same as those in Example 1, except for the types of esterification and polymerization catalysts (titanium catalysts), the timing of addition and the amount thereof, and the polymerization process parameters. The details are as follows:
[0115] PETG polymerization:
[0116] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0117] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.93:0.32 and a total molar ratio of PTA:(EG+CHDM) = 1:1.25. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 3ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was then fed through a screw meter. The liquid is pumped to the first esterification kettle, and the temperature in the first esterification kettle is controlled at 254-255°C. The pressure of the process tower is 70-80kpa (positive pressure). The second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. Titanium catalyst tetrabutyl titanate is added to the third chamber of the second esterification kettle as a polymerization catalyst. The polymerization catalyst accounts for 20ppm (in terms of titanium element) of the total mass of the melt. Toner and stabilizer (phosphate ester, etc.) are added to the third chamber of the esterification kettle. The second esterification kettle is a normal pressure reactor with three sub-chambers. The temperature is controlled as follows: 255-256°C in the first chamber, 253-254°C in the second chamber, and 257-258°C in the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs, and the reaction temperature of the first prepolymerization kettle is controlled at 260-261°C and the vacuum degree is 9.0Kpa; the oligomers after polymerization in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor, and the reaction temperature of the second prepolymerization kettle is controlled at 261-262°C. The prepolymer after the two-reactor reaction is introduced into the high-viscosity final polymerization reactor through the prepolymer melt pump and the prepolymer filter. The high-viscosity final polymerization reactor is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 265-267°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 630-650 Pa.s, and the outlet PETG intrinsic viscosity is controlled at 0.780 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PETG slice indicators are shown in Table 1 below.
[0118] Or PCTG polymerization:
[0119] Continuous polymerization is carried out on a 30,000 ton / year PCTG continuous polymerization unit, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.
[0120] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.63:0.63, and a total molar ratio of PTA:(EG+CHDM) = 1:1.26. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 5ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was delivered by a screw metering pump. To the esterification kettle, control the temperature in the esterification kettle at 256-257°C, the process tower pressure: 70-80kpa (positive pressure), the esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives, add titanium catalyst tetrabutyl titanate in the third chamber of the esterification kettle, as a polymerization catalyst (the addition of the second chamber is conducive to evaporating the water in the catalyst), the polymerization catalyst accounts for 20ppm (in terms of titanium element) of the total mass of the melt, add toner and stabilizer (phosphate ester, etc.) in the third chamber of the esterification kettle, and the esterification kettle is a normal pressure reaction The esterification temperatures of the three chambers are controlled as follows: 255-256°C for chamber 1, 253-254°C for chamber 2, and 260-262°C for chamber 3; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs, and the reaction temperature of the first prepolymerization kettle is controlled at 266-268°C, and the vacuum degree is 9.0Kpa; the oligomers polymerized in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor, and the reaction temperature of the second prepolymerization kettle is controlled at 271-273 ℃, the prepolymer after the reaction in the second prepolymerization kettle is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 277-278℃, the vacuum degree is 90-110Pa, the outlet melt dynamic viscosity is controlled at 610-630Pa.s, and the outlet PCTG intrinsic viscosity is controlled at 0.800 (measured in a mixed solvent with a volume ratio of phenol:tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.
[0121] The polyester melts obtained in each embodiment and comparative example were sliced, and the various properties of the slices were tested using the GB / T 14190-2017 standard. The results are shown in Tables 1-2 below, where IV refers to the intrinsic viscosity, which is measured in a mixed solvent of phenol and tetrachloroethane with a volume ratio of 3:2. DEG, H 2 O, ash, Fe, and agglomerated particles refer to the mass fraction contents of diethylene glycol, water, ash, Fe element, and agglomerated particles in polyester, respectively.
[0122] Table 1 Physical and chemical indicators of PETG
[0123]
[0124] Table 2 Physical and chemical indicators of PCTG
[0125]
[0126]
[0127] It can be seen that when the specific soluble germanium chelate catalyst of the present invention is used to catalyze the polymerization of PETG or PCTG, the viscosity of the obtained copolyester product is high and the color is excellent, which is better than the traditional germanium dioxide catalyst, titanium catalyst or titanium-antimony composite catalyst, or when citric acid is used, because citric acid is a tribasic acid, in addition to the two carboxyl groups used for germanium chelation, the germanium chelate also has a free carboxyl group, which will slightly affect the color of the copolyester product, making its color equivalent to that of the traditional catalyst, but the solubility and stability of the catalyst are significantly improved, and the long-term operation of the polymerization device is not affected. And the catalyst of the present invention has higher catalytic activity and better catalytic efficiency. When achieving the same catalytic efficiency, the amount of the traditional germanium catalyst can be reduced, thereby reducing the catalyst cost. And the method of removing the acid by recrystallization is higher than the method of removing the acid by adding a Lewis base, and the purity of the obtained catalyst is higher and the catalytic efficiency is higher.
[0128] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A soluble germanium chelate catalyst is used for catalyzing the synthesis of PETG / PCTG polyester, characterized in that: The use comprises the following steps: reacting germanium dioxide with an aqueous solution of an acid to generate a clear solution containing a germanium chelate, wherein the clear solution includes an excess of acid; adding a Lewis base to the clear solution to neutralize the excess acid to obtain an aqueous solution of the germanium chelate; and post-treating the aqueous solution of the germanium chelate to obtain the soluble germanium chelate catalyst; The acid is selected from tartaric acid, glutamic acid or oxalic acid; The Lewis base is selected from one or more combinations of sodium acetate, calcium acetate, zinc acetate, lithium acetate, manganese acetate, cobalt acetate, sodium carbonate, and sodium bicarbonate.
2. The use according to claim 1, characterized in that: The structure of the germanium dioxide is selected from hexagonal, anatase or amorphous.
3. The use according to claim 1, characterized in that: The particle size of the germanium dioxide is 0.1-75 μm.
4. The use according to claim 1, characterized in that: The molar ratio of the germanium dioxide to the acid is 1:1.0-5.
0.
5. The use according to claim 1, characterized in that: The reaction is carried out at 30-100° C.; and / or the reaction time is 2-6 hours.
6. The use according to claim 1, characterized in that: The mass concentration of the germanium chelate in the aqueous solution of the germanium chelate is 0.5-12.0%; the post-treatment comprises the step of adding ethylene glycol to the aqueous solution of the germanium chelate to obtain a water / ethylene glycol mixed solution of the germanium chelate.
7. The use according to claim 1, characterized in that: After adding Lewis base for neutralization, the pH value of the clear solution is 5.5-7.
0.
8. The use according to claim 1, characterized in that: The reaction is carried out in a reactor equipped with a reflux cooling system, and the water vapor generated by the reaction refluxes into the reactor; as the reaction proceeds, germanium dioxide gradually reacts to generate germanium chelate and dissolves in water, and the reaction system gradually changes from a white suspension to a clear and transparent state.
9. The use according to claim 1, characterized in that: The post-treatment includes the steps of cooling the aqueous solution of the germanium chelate, standing it for crystallization, filtering, washing and drying it to obtain germanium chelate crystals.
10. The use according to claim 9, characterized in that: The temperature after cooling is -20 to 0°C; and / or, the washing is carried out in anhydrous alcohol at 50 to 70°C, and the excess acid is further removed by washing.
11. The use according to claim 10, characterized in that: The washing time is 2 to 4 hours; during washing, the mass ratio of the crystal to the anhydrous alcohol is 1:1 to 2.
12. The use according to claim 9, characterized in that: The post-treatment also includes the steps of dissolving the germanium chelate crystals in a certain amount of water under stirring conditions at 60-80° C., adding ethylene glycol after complete dissolution, and continuing to stir evenly to obtain the soluble germanium chelate catalyst; and / or, in the soluble germanium chelate catalyst, the mass ratio of water to ethylene glycol is 1:4-4:
1.
13. The use according to claim 12, characterized in that: In the soluble germanium chelate catalyst, the mass concentration of the germanium chelate is 0.5% to 14.0%.
14. The use according to claim 1, characterized in that: During polyester synthesis, the soluble germanium chelate catalyst is used alone, or the soluble germanium chelate catalyst is used together with a titanium-based catalyst.
15. The use according to claim 14, characterized in that: The soluble germanium chelate catalyst is used alone as an esterification catalyst and a polymerization catalyst, and the esterification catalyst accounts for 5 to 15 ppm of the polymer mass, and the polymerization catalyst accounts for 50 to 70 ppm of the polymer mass, calculated as germanium dioxide; or, the soluble germanium chelate catalyst is used together with a titanium-based catalyst, and the titanium element in the titanium-based catalyst and the germanium element in the soluble germanium chelate catalyst account for 1 to 35 ppm and 150 to 10 ppm of the polymer mass, respectively.
Citation Information
Patent Citations
Method for producing polycyclohexylenedimethylene terephthalate resin having excellent coloring property and polycyclohexylenedimethylene terephthalate resin produced thereby
CN104640905A
Copolyester of cyclohexanedimethanol and process for producing such polyester
CN1121727A
A composite catalyst, a preparation method thereof, and polycyclohexyl terephthalate prepared therefrom.
CN113429549B
A method for preparing modified PETG copolyester using quaternary ammonium salt titanium / zirconium chelate catalysts
CN116693830B
Complexes of germanium with amino acids and carboxylic acids and method for preparing same
CN104203965A